Immunization status of children upto 3 years in rural block, Muzaffarnagar - Shankar, Rama; Muzammi, Khursheed; Kumar, Shailendra; Singh, Jai Veer (Indian Journal of Community Health, 2015)
Background: The year 2012-2013 was declared as ‘Year of intensification of Routine Immunization (IRI) in India. As per CES, DLHS and AHS, Full Immunization for the children of age group of 12-23 months of Uttar Pradesh is 30.2 (DLHS 2007), 40.9 (CES 2009) and 45.3 (AHS 2010-2011). Studies have been done to assess the primary immunization status i.e. BCG, OPV3, DTP3 and Measles. Data on the Booster doses and the additional vaccine is insufficient. Objectives: To assess the status of full Immunization, Complete Immunization and the status of Immunization with regard to different vaccine and reasons for partial and No Immunization. Design & Methodology: A community based cross sectional study was done (Aug to December 31th 2014) in the field practice area of rural health and training centre (RHTC) of Muzaffarnagar Medical College, Muzaffarnagar. 50% of the villages i.e. 3 villages (Bilaspur, Shernagar and Dhandhera) selected by simple random sampling technique and the age group selected were up to three years of age. The data was analyzed using MS excel sheet and the software used was software Epi-info version 7.1.3. Results and Conclusion: The Full Immunization in the age group of children between 12-23 months was 65% with antigen coverage maximum for BCG (93%) and lowest for Measles (68%). Reason for partial and unimmunized children were majority due to non-availability of vaccine at the centre followed by fear of AEFI. Complete Immunization in the age group between 24-36 months was 46% with MCV 2 coverage being the lowest (34%). Full Immunization in the age group of 24-36 months is significantly more than 12-23 months age group. Tendency is to have less and less immunization as the age of the child grows (P<0.05).